Adsorption of Cd and Ni from water by graphene oxide and graphene oxide–almond shell composite. (30th January 2019) - Yari Moghaddam, Nasibeh; Lorestani, Bahareh; Cheraghi, Mehrdad; Jamehbozorgi, Saeed
Abstract: The present study describes the preparation and capability of the graphene oxide/almond shell (GO@AS) composite by a freeze‐drying method. The composite showed excellent ability to uptake nickel and cadmium ions, which were characterized by Fourier transform infrared spectrum and scanning electron microscopy techniques. The optimized values of pH, contact time, and adsorbent doses were found to be 7.5, 30–180 min, and 0.1 g, respectively. Also, adsorption isotherms of metal ions on adsorbents were determined and correlated with common isotherm equations such as Langmuir and Freundlich models. The maximum sorption capacities of GO@AS calculated from Langmuir isotherm model were 121.95 mg/g for Cd (II) and 69.93 mg/g for Ni (II). A higher adsorption capacity was for Cd (II) on GO@AS. Practitioner points: Synthesis of graphene oxide–almond shell composite. Removal of Cd and Ni ions from water by graphene oxide–almond shell composite. Study of isotherm adsorption models.